2004
DOI: 10.1021/bi048938i
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase Triple-Helical Peptidase Activities Are Differentially Regulated by Substrate Stability

Abstract: Matrix metalloproteinases (MMPs) are involved in physiological remodeling as well as pathological destruction of tissues. The turnover of the collagen triple-helical structure has been ascribed to several members of the MMP family, but the determinants for collagenolytic specificity have not been identified. The present study has compared the triple-helical peptidase activities of MMP-1 and MMP-14 (membrane-type 1 MMP; MT1-MMP). The ability of each enzyme to efficiently hydrolyze the triple helix was quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 76 publications
(156 reference statements)
9
88
0
Order By: Relevance
“…The hydrolysis of fTHP-15 by each of these MMPs has been reported previously (8,17,18,35,45) and occurs at the GlyϳLeu bond. Thus, fTHP-15 served as a well established point of reference.…”
Section: Peptidementioning
confidence: 55%
See 2 more Smart Citations
“…The hydrolysis of fTHP-15 by each of these MMPs has been reported previously (8,17,18,35,45) and occurs at the GlyϳLeu bond. Thus, fTHP-15 served as a well established point of reference.…”
Section: Peptidementioning
confidence: 55%
“…These melting temperatures indicate fTHP thermal stabilities suitable for MMP kinetic analyses. The three fTHPs had similar stabilities, an important consideration as prior studies have shown that MMP hydrolytic activity toward both THPs and collagens can vary greatly due to differences in substrate thermal stability (35,41). The close similarity of thermal stability among the three fTHPs warranted our continued analysis of the effects of sequence variations.…”
Section: Peptidementioning
confidence: 99%
See 1 more Smart Citation
“…We used the collagen model substrate [Gly-Pro-4-hydroxyproline (Hyp)] 5 -Gly-Pro-Lys(7-methoxycoumarin-4-yl)-Gly-Pro-Gln-GlyCys(4-methoxybenzyl)-Arg-Gly-Gln-Lys(2,4-dinitrophenyl)-Gly-ValArg-(Gly-Pro-Hyp) 5 -NH 2 as an optimized recognition sequence for MT1-MMP (26,27). This substrate is biologically active and exhibits self-assembly capability to form triple-helical collagen-like monomers from its single-chain cognate peptide (13.5 kDa).…”
Section: Resultsmentioning
confidence: 99%
“…The FRET peptide (Gly-ProHyp) 5 -Gly-Pro-Lys(7-methoxycoumarin-4-yl)-Gly-Pro-Gln-Gly-Cys(4-methoxybenzyl)-Arg-Gly-Gln-Lys(2,4-dinitrophenyl)-Gly-Val-Arg-(Gly-Pro-Hyp) 5 -NH 2 was synthesized as described previously (26). Nonfluorogenic peptide substrates (for XAS experiments) were synthesized by Genscript.…”
Section: Methodsmentioning
confidence: 99%